2020
DOI: 10.1002/advs.201903616
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Deficiency Impairs Mitophagy and Promotes Inflammasome Activation and Mammary Tumor Metastasis

Abstract: The breast cancer susceptibility gene 1 (BRCA1) is a major tumor suppressor gene and is most frequently mutated in hereditary breast cancer. BRCA1 plays a critical role in many biological processes, especially maintaining genomic stability in the nucleus, yet its role in the cytoplasm remains elusive. Here, it is revealed that BRCA1 maintains a healthy mitochondrial network through regulating mitochondrial dynamics, including fission and fusion. BRCA1 deficiency causes dysfunctional mitochondrial dynamics thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 62 publications
(95 reference statements)
4
48
0
Order By: Relevance
“…This is consistent with a possible defect in mitochondrial fusion/fission in A-T cells. A recent report shows that BRCA1 deficiency results in a higher level of MFN1/2 protein expression, accelerating mitochondrial fusion, which can block the separation of damaged mitochondria from healthy ones and negatively affect mitophagy ( Chen et al., 2020 ). In addition, clearing damaged mitochondria is defective in Atm-deficient cells and increasing intracellular NAD+ is associated with improving mitochondrial quality via mitophagy ( Valentin-Vega et al., 2012 ; Fang et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with a possible defect in mitochondrial fusion/fission in A-T cells. A recent report shows that BRCA1 deficiency results in a higher level of MFN1/2 protein expression, accelerating mitochondrial fusion, which can block the separation of damaged mitochondria from healthy ones and negatively affect mitophagy ( Chen et al., 2020 ). In addition, clearing damaged mitochondria is defective in Atm-deficient cells and increasing intracellular NAD+ is associated with improving mitochondrial quality via mitophagy ( Valentin-Vega et al., 2012 ; Fang et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…NF- κ B is essential for NLRP3 inflammasome activation, and the findings from us and other laboratories demonstrated that NF- κ B inhibition was sufficient to alleviate the activation of NLRP3 inflammasome [ 34 ]. Moreover, results from Chen et al revealed that AMPK α regulated dynamin-related protein 1-mediated mitochondrial fission and thereby restrained NLRP3 inflammasome activation [ 49 ]. Collectively, our data defined miR-31-5p as a promising therapeutic target for the treatment of ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Globular adiponectin has been shown to decrease BC cell growth as a result of NLRP3 inflammasome inhibition (82). An in vitro/in vivo study showed that BRCA1 deficit affected mitochondrial function, mitophagy and NLRP3 inflammasome activation, thus promoting metastasis (83). The findings of these studies provide evidence that inflammasome inhibition could serve as a therapeutic target for the treatment of BC.…”
Section: Inflammasomes and Bcmentioning
confidence: 91%